Changes in Microbiological and Physicochemical Quality of Dried Persimmons (Diospyros kaki Thunb.) Stored at Various Temperatures. (18th August 2019) - Hyun, Jeong-Eun; Kim, Ji-Yeon; Kim, Eun-Mi; Kim, Jong-Chan; Lee, Sun-Young
Abstract : This study was conducted to investigate the microbiological, physicochemical, and visual quality of dried persimmons ( Diospyros kaki Thunb. cv. Cheongdo-Bansi) during storage at various temperatures in order to determine the shelf-life. Two commercial dried persimmon samples were evaluated for changes in weight, moisture content, color, texture (hardness and gumminess), and microbial populations during storage at different temperatures (−20, 5, 12, and 25°C) for 70 days. Overall, dried persimmon-2 showed lower levels of total mesophilic bacteria, Escherichia coli, coliforms, yeasts, and molds than dried persimmon-1. Among the physicochemical qualities, significant differences were observed in color parameters such asL ∗, a ∗, andb ∗ of the dried persimmons. However, no significant differences in weight, moisture content, and texture were observed in dried persimmons during storage for 70 days. Thus, changes in visual appearance and color index such as chroma value and browning index can be used as indicators for determining the shelf-life of dried persimmons.